Lean Software Startup – an Experience Report from an Entrepreneurial Software Business Course - Antero Järvi; Ville Taajamaa; Sami Hyrynsalmi (Switzerland, 2025)
This paper offers blueprints for and reports upon three years experi-ence from teaching the university course “Lean Software Startup” for information technology and economics students. The course aims to give a learning experience on ideation/innovation and subsequent product and business development using the lean startup method. The course educates the students in software business, entrepreneurship, teamwork and the lean startup method. The paper describes the pedagogical design and practical implementation of the course in sufficient detail to serve as an example of how entrepreneurship and business issues can be integrated into a software engineering curriculum. The course is evaluated through learning diaries and a questionnaire, as well as the primary teacher’s learnings in the three course instances. We also examine the course in the context of CDIO and show its connection points to this broader engineering education framework. Finally we discuss the challenges and opportunities of engaging students with different backgrounds in a hands-on entrepreneurial software business course.
Software Business – 6th International Conference, ICSOB 2015, Braga, Portugal, June 10-12, 2015, Proceedings